2019
DOI: 10.20944/preprints201905.0386.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mysterious, and Potentially Revolutionary, Immunological Properties of Transfer Factor: A Review

Abstract: Transfer factor is the name given to material derived from activated lymphocytes that is probably composed of a complex of a peptide and a short segment of RNA and which has the reported ability to transfer specific T cell immunity to uncommitted lymphocytes. Many independent groups around the world reported isolating transfer factors between 1955 and 1990 and demonstrating their ability to transfer passive immunity from one animal or individual to another, often within 24 hours of inoculation. Such activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…A variety of groups have, over many decades, suggested that such a mechanism might exist and provided arguments for why such a mechanism might be required in place of the textbook mechanism of random clonal production of every possible TCR or antibody sequence (e.g., [167][168][169][170][171][172][173]. This is not the place to provide a detailed description of how such a mechanism might work or the data and logical arguments that might support such a mechanism (some of which are provided in [174,175]). However, in the spirit of examining all possible hypotheses that can explain TCR mimicry of AD-inducing antigens, antigen templating of the hypervariable region is compatible with the results reported here.…”
Section: Explaining the Results 5: Antigen Templating Of The Hypervar...mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of groups have, over many decades, suggested that such a mechanism might exist and provided arguments for why such a mechanism might be required in place of the textbook mechanism of random clonal production of every possible TCR or antibody sequence (e.g., [167][168][169][170][171][172][173]. This is not the place to provide a detailed description of how such a mechanism might work or the data and logical arguments that might support such a mechanism (some of which are provided in [174,175]). However, in the spirit of examining all possible hypotheses that can explain TCR mimicry of AD-inducing antigens, antigen templating of the hypervariable region is compatible with the results reported here.…”
Section: Explaining the Results 5: Antigen Templating Of The Hypervar...mentioning
confidence: 99%
“…The first involves initiating T1DM in Lewis rats by infecting them with Kilham rat virus (KRV). KRV increased intestinal Bifidobacterium and Clostridium species [178] in parallel with T1DM development such that antibiotic treatment not only prevented the increase in Bifidobacterium and Clostridium abundance but also prevented the onset of T1DM [175]. Similarly, the susceptibility of NOD mice to the development of T1DM depends on gut Clostridial butyrate biosynthesis species [179].…”
Section: Elucidating Ad Etiologies From Tcr Sequences To Develop Nove...mentioning
confidence: 99%